Coupling of anhydro-aldose tosylhydrazones with hydroxy compounds and carboxylic acids: a new route for the synthesis of C-β-d-glycopyranosylmethyl ethers and esters. Issue 17 (7th February 2017) - Kaszás, Tímea; Tóth, Marietta; Kun, Sándor; Somsák, László
Abstract : Cross coupling of anhydro-aldose tosylhydrazones gave new access to C -glycopyranosylmethyl ethers and esters. Abstract : Cross couplings of O -peracylated 2, 6-anhydro-aldose tosylhydrazones ( C -(β-d -glycopyranosyl)formaldehyde tosylhydrazones) with alcohols, phenols, and carboxylic acids were studied under thermic or photolytic conditions in the presence of K3 PO4 or LiO t Bu. The reactions failed with EtOH, BnOH, or t BuOH, however, (CF3 )2 CHOH, electron poor phenols and carboxylic acids gave the corresponding C -β-d -glycopyranosylmethyl ethers and esters, respectively, representing a new access to these glycomimetic compounds.